Main Risk Factors of Myocardial Infarction - Urmanbekova Dilfuza Sanatullayevna; Bozorov Murodjon Baxtiyor o’gli; Elmurotova Dilnoza Baxtiyorovna (American Journal of Bioscience and Clinical Integrity, 2025)
At work myocardium heart attack of the disease come exit causes development mechanism, clinical signs and modern diagnosis methods illuminated. Myocardium heart attack coronary blood of the flow sharp violation as a result heart muscles ischemia and to necrosis meeting with is described. Also, acute in the period to be displayed fast medical help, thrombolytic treatment, stenting and rehabilitation measures about information given.